Long-term effects of adenoidectomy and tonsillectomy on frequency and severity of acute respiratory infections in children: a systematic review - Collazos, Sergio Molina; Mancero, Fernando Rafael Chico; Barros, José Javier Guzmán; Cáceres, Angie Carolina Villamizar; Valdés, Sofía Isabella Figueroa (International Journal of Research in Medical Sciences, 2024)
Adenoidectomy and tonsillectomy are common surgical procedures performed in children to reduce chronic infections and address obstructive sleep apnea. While these surgeries typically lower the frequency of acute infections initially, they have been associated with an increased risk of respiratory illnesses in later life. This study aimed to evaluate existing research on the long-term impact of these surgeries on respiratory health. A systematic review was conducted using databases such as Cochrane Library, PubMed, and Google Scholar, focusing on studies published from 2000 to 2024. The targeted population was children under 14 years, with a minimum follow-up of 12 months. The analysis included clinical trials, cohort studies, and meta-analyses. Results showed mixed outcomes: adenoidectomy significantly reduced sinusitis episodes from 3.8 to 1.2 per year (p<0.001). However, tonsillectomy was linked to a 2.72-fold increase in respiratory disease risk and a 17% rise in infectious diseases (RR: 1.17). Additionally, adenotonsillectomy was associated with an increased asthma risk (HR: 2.25). In conclusion, while adenoidectomy may reduce sinusitis frequency, tonsillectomy and adenotonsillectomy are linked to elevated risks of long-term respiratory and infectious diseases. These findings highlight the importance of carefully weighing the potential long-term consequences of these surgeries when considering interventions for pediatric respiratory conditions.